Multi-institutional study of the frequency, genomic landscape, and outcome of IDH-mutant glioma in pediatrics. Issue 1 (23rd May 2022) - Yeo, Kee Kiat; Alexandrescu, Sanda; Cotter, Jennifer A; Vogelzang, Jayne; Bhave, Varun; Li, Marilyn M; Ji, Jianling; Benhamida, Jamal K; Rosenblum, Marc K; Bale, Tejus A; Bouvier, Nancy; Kaneva, Kristiyana; et al.
Abstract: Background: The incidence and biology of IDH1/2 mutations in pediatric gliomas are unclear. Notably, current treatment approaches by pediatric and adult providers vary significantly. We describe the frequency and clinical outcomes of IDH1/2 -mutant gliomas in pediatrics. Methods: We performed a multi-institutional analysis of the frequency of pediatric IDH1/2 -mutant gliomas, identified by next-generation sequencing (NGS). In parallel, we retrospectively reviewed pediatric IDH1/2 -mutant gliomas, analyzing clinico-genomic features, treatment approaches, and outcomes. Results: Incidence: Among 851 patients with pediatric glioma who underwent NGS, we identified 78 with IDH1/2 mutations. Among patients 0–9 and 10–21 years old, 2/378 (0.5%) and 76/473 (16.1%) had IDH1/2 -mutant tumors, respectively. Frequency of IDH mutations was similar between low-grade glioma (52/570, 9.1%) and high-grade glioma (25/277, 9.0%). Four tumors were graded as intermediate histologically, with one IDH1 mutation. Outcome: Seventy-six patients with IDH1/2 -mutant glioma had outcome data available. Eighty-four percent of patients with low-grade glioma (LGG) were managed observantly without additional therapy. For low-grade astrocytoma, 5-year progression-free survival (PFS) was 42.9% (95%CI:20.3–63.8) and, despite excellent short-term overall survival (OS), numerous disease-related deaths after year 10 were reported. Patients with high-grade astrocytoma had a 5-year PFS/OS of 36.8% (95%CI:8.8–66.4) and 84% (95%CI:50.1–95.6), respectively. Patients with oligodendroglioma had excellent OS. Conclusions: A subset of pediatric gliomas is driven by IDH1/2 mutations, with a higher rate among adolescents. The majority of patients underwent upfront observant management without adjuvant therapy. Findings suggest that the natural history of pediatric IDH1/2 -mutant glioma may be similar to that of adults, though additional studies are needed.